Public spaces and gender in spanish historical centres: the Alamedas of Seville and Santa Cruz de Tenerife - Luz Marina García Herrera María Del Carmen Díaz Rodríguez, Antonio García García, Alejandro Armas Días (Boletín de la Asociación de Geógrafos Españoles)
Resumen